The Marcel Marceau counting book - Mendoza, George; Greene, Milton H. (Garden City, N.Y. : Doubleday, 1971)
Mime Marcel Marceau wears twenty different hats representing twenty different professions. Color photographs.
Keywords: Marceau, Marcel, -- 1923-2007.; Counting; Picture books